2007
DOI: 10.1037/0735-7036.121.4.447
|View full text |Cite
|
Sign up to set email alerts
|

Learning to learn during visual discrimination in group housed dwarf goats (Capra hircus).

Abstract: Using an automated learning device, we investigated "learning to learn" by dwarf goats (Capra hircus) in what was for them a familiar environment and normal social settings. Nine problems, each consisting of four discriminable black symbols, each with one S-super+ and three different S-super(-), were presented on a computer screen. Mean daily learning success improved over the course of the first four problems, and the improvement was maintained throughout the remaining five problems. The number of trials to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Species-specific information is necessary for development of training programs because innate predispositions are likely to differ depending on the environments where behaviors evolved. For example, Langbein et al, (2007a) determined that goats have a preference for certain symbols, and that learning can be enhanced or slowed depending on which symbols are associated with the reward. Moreover, the ability to learn tasks that depend on discrimination of stimuli depends on perceptual ability, which is typically different among species.…”
Section: Operant Conditioningmentioning
confidence: 99%
“…Species-specific information is necessary for development of training programs because innate predispositions are likely to differ depending on the environments where behaviors evolved. For example, Langbein et al, (2007a) determined that goats have a preference for certain symbols, and that learning can be enhanced or slowed depending on which symbols are associated with the reward. Moreover, the ability to learn tasks that depend on discrimination of stimuli depends on perceptual ability, which is typically different among species.…”
Section: Operant Conditioningmentioning
confidence: 99%
“…Both problems contained the jagged-margin symbol, and performance was lowest in N15 when this symbol was used as the rewarded symbol. We know from the previous studies that dwarf goats possess an outstanding ability to discriminate complex symbols (Langbein et al 2007a(Langbein et al , 2008. However, in these studies, we also found that goats sometimes had diYculties in discriminating or avoiding a speciWc symbol.…”
Section: Transfer Testmentioning
confidence: 52%
“…Only the Wrsttrial performance for each new problem was analysed during the transfer test. (Hanggi 1999;Langbein et al 2007a). The number of trials per individual and per day was always greater than 20 (mean 71.1 § 11.2).…”
Section: Transfer Testmentioning
confidence: 97%
See 2 more Smart Citations